Determinants of Non-Performing Loans in Cyprus: An Empirical Analysis of Macroeconomic and Borrower-Specific Factors - Christodoulou-Volos, Christos (International Journal of Economics and Financial Issues, 2024)
This study empirically investigates the determinants of non-performing loans (NPLs) within the Cypriot banking sector by employing Pearson’s correlation analysis and Generalized Method of Moments (GMM) estimations. Utilizing a sample of 200 NPLs granted to individuals by a Cypriot banking institution from 2013 to 2019, the study examines both macroeconomic and borrower-specific factors influencing NPLs. The findings reveal significant associations between borrower profile characteristics - such as gender, age, education level, professional and financial standing, and place of residence - and loan-specific details, including loan purpose, type of collateral, and NPL status and rescheduling. The study also identifies that lower economic growth, higher inflation, and higher interest rates correlate with an increase in NPLs. Moreover, borrower-specific variables like return on assets and loan growth significantly affect NPL levels. These results offer valuable insights into management in taking corrective actions and have important policy implications for regulatory authorities in formulating effective economic policies. Additionally, the study guides potential investors by highlighting key risk factors associated with NPLs in Cyprus.